Análise dos determinantes do valor agregado da indústria de construção civil no Brasil - Silva, José Almir da (2017)
This paper intends to demonstrate that the construction industry is a key sector within the Brazilian economic structure, producing a chaining effect between sectors of the economy, creating positive externalities capable of increasing the productivity of the factors of production and significantly stimulating the growth of the economy national product. To answer this question, this work will analyze the trends of some determinants for the performance of Civil Construction production, between the years 2011 and 2015, through the presentation of conceptual aspects about the sector and analysis of indicators of production, employment, cost of construction market, financing rates, volume of credit granted, population, specified through an econometric model. The strategy adopted was that of panel data in light of the information available, which consists of combining data from cross-sectional cohorts with time series. This strategy, in addition to allowing a greater number of samples, allows us to control unobservable, time - bound effects by addressing the problem in three ways: pooled model, fixed effects model and random effects model. It follows from the results that the selected variables contribute satisfactorily to explain the dynamics of the civil construction sector, demonstrating the importance of acting, both the state, through incentive policies, and the private initiative that is directly or indirectly affected by it.